PENYUSUNAN MODEL PENDUGA VOLUME POHON JENIS JELUTUNG RAWA (Dyera polyphylla (Miq) V. Steenis) - Qirom, Muhammad Abdul; Supriyadi, Supriyadi (Jurnal Penelitian Hutan Tanaman, 2012)
ABSTRACTThe development of of Dyera polyphylla trees requires complete information on the estimated yield. The estimated yield or volume can be obtained by using an estimating equation for the tree volume.The objectives was to obtain of the best estimation models for the total and merchantable volumes of D. polyphylla trees. The volume estimation models were formulated using 96 selected tree samples representing the whole stand populations. Sample trees were measured using Spiegel Relascop Bitterlich (SRB). The estimator models tested consist of linear and non-linear models with a single variable (diameter) and double variables (diameter and height of the tree). The results of this study indicated that diameter as the single variable can be used to formulate an estimator model for both the total and merchantable volumes of trees. However, the addition of the height variable into the model is still needed. The estimation models of tree volumes with two variables (diameters and heights) were used to obtain a standard volume table. The determination coefficient rose less than 2% compared to the model with the diameter variable. The best model of tree volume estimators with either one or two variables has high coefficient (> 80%) of determination (R2). The best models of estimating total tree volume are 1) with the use of diameter as a single variable: Ln Volume 7.9444Â Â Â Â  Â 2.1952 * Â Ln DiameterÂ  Â Â and 2) with the use of diameter and height as double variables: Volume =2.4081*10-4*(Diameter2.Height)0.80871. The best models to estimate the volume of merchantable trees are 1) with the use of diameter variable: Ln Volume = 8.2598+(2.2843)*(Ln(Diameter)), and 2) with the use of diameter and height as the variables: Ln Volume = 9.0589+(1.8958)*(Ln)Diameter))+(0.7347) *(Ln(Height))ABSTRAKPengembangan jenis Jelutung Rawa membutuhkan informasi yang lengkap terkait perkiraan hasil yang akan diperoleh. Perkiraan hasil dapat diperoleh dengan menduga volume tegakan menggunakan persamaan penduga volume pohon. Penelitian ini bertujuan mendapatkan model-model penduga volume terbaik jenis Jelutung Rawa untuk volume pohon total dan volume kayu yang dapat diperdagangkan. Penyusunan model penduga volume ini menggunakan 96 sampel pohon terpilih yang mewakili kondisi tegakan secara keseluruhan. Pohon sampel tersebut diukur dengan menggunakan Spiegel Relaskop Bitterlich (SRB) sehingga sampel pohon tidak ditebang. Model- model penduga pohon yang diujicobakan terdiri dari model linear dan non-linear dengan peubah tunggal (diameter) dan ganda (diameter dan tinggi pohon). Hasil penelitian ini menunjukkan penggunaan diameter sebagai peubah tunggal dapat digunakan menyusun model penduga volume pohon baik volume total maupun volume kayu yang dapat diperdagangkan. Namun demikian, penambahan variabel tinggi kedalam model tetap diperlukan. Model penduga volume pohon dengan dua variabel diameter dan tinggi digunakan untuk menyusun tabel volume standar. Koefisien determinasi naik < 2% dari model dengan peubah diameter. Model terbaik penduga volume baik satu atau dua peubah mempunyai R2Â Â  yang tinggi (> 80%). Model terbaik untuk menduga volume pohon total yakni 1) menggunakan peubah tunggal (diameter): Ln Volume = â7,9444 + (2,1952) * (Ln (Diameter)); dan 2) menggunakan peubah ganda (diameter dan tinggi): volume = 2,4081 * 10-4Â  * (Diameter2.Tinggi)0,80871. Model terbaik untuk menduga volume pohon merchantable yakni 1) menggunakan peubah diameter: Ln Volume = â 8,2598 + (2,2843) * (Ln (Diameter)); 2) menggunakan peubah diameter dan tinggi:Ln Volume = â 9,0589 + (1,89958) * (Ln (Diameter)) + (0,7347) * (Ln(tinggi)).